PENERAPAN HIERARKI PERATURAN PERUNDANG-UNDANGAN DALAM KETATANEGARAN INDONESIA - Bambang Antariksa (deliberatif, 2017)
Based on the theory of the hierarchical structure of the legal system, states that the legal system is a tiered and layered in a structure (hierarchy). This paper discusses application of hierarchy of Laws and Regulations in Indonesia. The results confirm that the implementation of hierarchy of laws and regulations has been employed in the legal system following the Indonesian state administration system. UUD 1945 (amendment) explicitly mentions the existence of hierarchy of laws and regulations through institutions examining the hierarchy of laws and regulations, namely the Constitutional Court and Supreme Court, as well as the Laws concerning the hierarchy of laws and regulations. Abstrak: Berdasarkan teori hierarki norma hukum, disebutkan bahwa norma hukum itu berjenjang dan berlapis dalam suatu tata susunan (hierarki). Tulisan ini membahas mengenai penerapan hierarki Peraturan Perundang-Undangan di Indonesia. Hasil Penelitian menunjukkan penerapan hierarki Peraturan Perundang-Undangan telah diterapkan didalam sistem hukum yang mengikuti sistem ketatanegaraan di Indonesia. UUD 1945 (amandemen) secara eksplisit menyebutkan adanya hierarki Peraturan Perundang-Undangan melalui lembaga yang menguji hierarki Peraturan Perundang-Undangan yaitu Mahkamah Konstitusi dan Mahkamah Agung, serta adanya Undang-Undang yang mengatur mengenai hierarki Peraturan Perundang-Undangan.